1985
DOI: 10.1111/j.1432-1033.1985.tb08616.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of activation and secretion of a cell‐associated precursor of an exocellular protease of Pseudomonas aeruginosa 34362A

Abstract: An inactive precursor to the active exocellular protease 1 of Pseudomonas aeruginosa is cell-associated and located primarily in the periplasmic space. We have studied factors that bring about activation of the precursor in vitro in order to shed some light on the process of its activation and secretion in vivo. A variety of diverse procedures were shown to effect irreversible activation. Several mild non-enzymatic procedures were effective, such as dialysis of an ammonium sulfate precipitate against neutral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…Our failure to detect enzymatically active elastase within MVs can be explained by previous work (12,28). It has been shown that the enzyme is first made as an inactive preproelastase in the cytoplasm and a proelastase in the periplasm (12,28,29). This proenzyme becomes modified as it crosses the outer membrane and becomes active.…”
Section: Discussionmentioning
confidence: 80%
“…Our failure to detect enzymatically active elastase within MVs can be explained by previous work (12,28). It has been shown that the enzyme is first made as an inactive preproelastase in the cytoplasm and a proelastase in the periplasm (12,28,29). This proenzyme becomes modified as it crosses the outer membrane and becomes active.…”
Section: Discussionmentioning
confidence: 80%
“…Previous attempts to purify this precursor resulted in its activation. Thus, the purified precursor and the elastase were indistinguishable, and the possibility was raised that activation did not result from proteolytic processing of the precursor itself, but rather that it involved the removal of a non-covalently associated elastase inhibitor (5). In the present study, we describe the purification of an inactive periplasmic elastase precursor that is structurally distinct from the elastase and demonstrate that activation involves proteolytic processing of the precursor itself.…”
mentioning
confidence: 92%
“…phospholipase activity (32) and an inactive elastase precursor (19,22) were demonstrated in the periplasmic fraction of P. aeruginosa cells. The inactive periplasmic elastase precursor is activated by controlled proteolysis (19,22), yet this precursor was reported to have the same molecular weight and the same N-terminal amino acid (alanine) as the extracellular elastase (7,8,19,24). Fecycz and Campbell (7) suggested that activation did not result from proteolytic processing of the precursor itself, but rather involved dissociation of the elastase from a non-covalently bound elastase inhibitor.…”
mentioning
confidence: 99%